EPSILON(B) CONSTRAINTS ON SELF-COUPLINGS OF VECTOR BOSONS - Eboli, OJP; Lietti, S. M.; Gonzalezgarcia, M. C.; Novaes, Sérgio Ferraz [UNESP] (Elsevier B.V., 1994)
We analyze the constraints on possible anomalous contributions to the W(+)W(-)Z vertex coming from non-universal radiative corrections to the Z --> b $($) over bar$$ b width. We parametrize these corrections in terms of epsilon(b) and use the LEP data to establish the allowed values for the anomalous triple couplings. We examine all CP conserving effective operators that exhibit SU(2)(L) x U(1)(Y) gauge invariance and do not give any tree level contribution to the present experimental observables. For some of these operators our constraints are comparable with the bounds coming from a global fit of the oblique parameters, which evidences the increasing relevance of the precise measurement of the b-quark parameters at LEP for the search of new physics.